Japan’s “Free and Open Indo-Pacific” strategy : Tokyo’s tactical hedging and the implications for ASEAN - Koga, Kei (2022)
This article argues that by creating a “Free and Open Indo-Pacific Strategy” (FOIPS) in 2016, Japan has engaged in “tactical hedging” to cope with the strategic uncertainty engendered by China’s growing economic power and political influence in Asia and the Trump administration’s uncertain foreign policy towards the region. Tactical hedging refers to a declaratory policy doctrine that aims to utilize temporal strategic ambiguity to understand and determine whether any long-term strategy shift is necessary or possible. In doing so, Japan has bided its time in order to understand strategic trends and coordinate policies and principles with allies and partners—especially the United States and ASEAN—and shaped the concept of a “Free and Open Indo-Pacific” (FOIP) in accordance with those consultations since 2016. Nevertheless, the emerging trend—especially the clear division between America’s more hardline stance towards China and ASEAN’s own conceptualization of the Indo-Pacific which aims to facilitate cooperation with China—indicates that the benefits of tactical hedging are diminishing, and that Japan needs to clarify its political stance if it wants to maintain its own FOIP concept as a viable strategic vision.